2019
DOI: 10.3390/ijerph16234877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Loss on FGF-21 in Human Subjects: An Exploratory Study

Abstract: Fibroblast growth factor-21 (FGF-21), is a protein involved in cell growth and differentiation, development, wound repair and metabolism. Research looking at the impact of weight loss on FGF-21 levels is limited. The objective of this exploratory study was to determine changes in serum FGF-21 levels following weight loss induced by either continuous energy restriction or intermittent energy restriction. A sub cohort of participants who completed a 12-month dietary intervention trial following continuous energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…However, in the current trial, weight loss did not result in a change in serum FGF-21. Similar to our study, Headland et al also reported no change in blood FGF-21 concentration in individuals following an energy restriction diet (of 1000 kcal/day for women or 1300 kcal/day for men) for 12 months [33]. In the present study, there was also no change in serum osteopontin, a multifunctional protein which is distributed in many tissues and fluids.…”
Section: Discussionsupporting
confidence: 90%
“…However, in the current trial, weight loss did not result in a change in serum FGF-21. Similar to our study, Headland et al also reported no change in blood FGF-21 concentration in individuals following an energy restriction diet (of 1000 kcal/day for women or 1300 kcal/day for men) for 12 months [33]. In the present study, there was also no change in serum osteopontin, a multifunctional protein which is distributed in many tissues and fluids.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, CRIWL significantly decreased the cFGF21 level (SMD=-0.51 pg/ml, 95%CI: -0.92 to -0.09, p=0.02) ( Figure 5 ). Among them, cFGF21 concentrations were significantly lower in individuals who underwent hypocaloric diets with relatively high protein contents (≥30% diet calorie from protein, ≥30E% protein) than their cFGF21 levels before the diets ( 32 36 ) (p=0.003); while CR with <30E% protein ( 36 40 ) or CR with unspecified protein content ( 32 , 41 , 42 ) did not significantly affected the cFGF21 level ( Figure 5 , p=0.30 and p=0.12 respectively). The heterogeneity among these studies was significant (p<0.00001).…”
Section: Resultsmentioning
confidence: 97%
“…Eleven studies containing 367 individuals were involved in the analysis of the association between calorie restriction (CR)-induced weight loss (CRIWL) and cFGF21 concentration ( 32 42 ) ( Table 4 ). Overall, CRIWL significantly decreased the cFGF21 level (SMD=-0.51 pg/ml, 95%CI: -0.92 to -0.09, p=0.02) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations